SIGNIFIKANSI TARIKH CIPTA DAN TERBIT DALAM PEMBACAAN TEKS - Nugraha, Dipa (UNIVERSITAS PGRI YOGYAKARTA, 2025)
This article discusses the important status of the time of creation and or publication of literary works in interpretation. This type of article is a literature review article. The sample cases of literary studies used are the cases of Serat Darmogandul, the novel Sitti Nurbaya, the poem